Bis(tetraethylammonium) oxalate dihydrate - Timothy J. McNeese; Robert D. Pike (Acta Crystallographica Section E, 2012)
The title compound, 2C8H20N+·C2O42−·2H2O, synthesized by neutralizing H2C2O4·2H2O with (C2H5)4NOH in a 1:2 molar ratio, is a deliquescent solid. The oxalate ion is nonplanar, with a dihedral angle between carboxylate groups of 64.37 (2)°. O—H...O hydrogen bonds of moderate strength link the O atoms of the water molecules and the oxalate ions into rings parallel to the c axis. The rings exhibit the graph-set motif R44(12). In addition, there are weak C—H...O interactions in the crystal structure.